2015
DOI: 10.1038/pr.2015.136
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent hypoinsulinemic hyperglycemia in neonatal rats increases PARP-1 and NF-κB expression and leads to microglial activation in the cerebral cortex

Abstract: Background: Hyperglycemia is a common metabolic problem in extremely low-birth-weight preterm infants. Neonatal hyperglycemia is associated with increased mortality and brain injury. Glucose-mediated oxidative injury may be responsible. Poly(ADP-ribose) polymerase-1 (PARP-1) is a nuclear enzyme involved in DNA repair and cell survival. However, PARP-1 overactivation leads to cell death. NF-κB is coactivated with PARP-1 and regulates microglial activation. The effects of recurrent hyperglycemia on PARP-1/NF-κB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 42 publications
6
32
0
Order By: Relevance
“…The volume of injection was 0.01 mL/g for the first injection and 0.005 mL/g for the second injection. Our previous study has demonstrated that this model induces hyperglycemia, beginning at 5 min after the first dextrose injection, with spontaneous resolution 120 min later, 14 likely due to stimulation of insulin secretion from the pancreas. Pups assigned to the P30-control group were subcutaneously injected with an equivalent volume of normal saline at the corresponding times.…”
Section: Induction Of Recurrent Hyperglycemiamentioning
confidence: 78%
See 4 more Smart Citations
“…The volume of injection was 0.01 mL/g for the first injection and 0.005 mL/g for the second injection. Our previous study has demonstrated that this model induces hyperglycemia, beginning at 5 min after the first dextrose injection, with spontaneous resolution 120 min later, 14 likely due to stimulation of insulin secretion from the pancreas. Pups assigned to the P30-control group were subcutaneously injected with an equivalent volume of normal saline at the corresponding times.…”
Section: Induction Of Recurrent Hyperglycemiamentioning
confidence: 78%
“…Loss of neurons (where Glu is predominantly localized) and/or increased number of astrocytes (where Gln is predominantly localized) is unlikely to explain the lower Glu/Gln ratio. The hyperglycemia model used in the present study is not associated with neuronal loss . Unchanged levels of NAA, the marker of neuronal integrity (Figure ), and unchanged astrocyte number (Supplementary Figure) in the hyperglycemia groups also rule out neuronal loss and/or astrocytosis as the explanation for decreased Glu/Gln ratio.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations